The Identification of Soil Insect in The Karandangan Natural Tourism Forest - Immy Suci Rohyani; Yunda Sulistiani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Live insects rely on their habitat. Soil serves as a place to live, defense and a source of food for soil insects. Soil insects act as decomposers of organic materials and can be used as indicators of soil fertility and determinants of the stability of an ecosystem. This study aims to identify the types of insects found in the Kerandangan Nature Tourism Park Forest. This research is descriptive exploratory, sampling by purposive sampling with pitfall trap method. The results obtained 18 families 27 genera with the number of individuals as many as 520 individuals. Formicidae had the most number of individuals, namely 297 individuals. The genera with the highest number of individuals were Oechophylla (154), Streblognathus (89), Alphitobius (75), Gryllus (48), Macrotermes (48).